The THE ROLE OF STRUCTURAL CHANGE IN BRAZILIAN STATES’ ECONOMIC GROWTH - Nepomuceno Pinto, Michele Aparecida; Silva da Cunha, Marina; Pais Gularte, Luis Carlos (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2024)
The spatial dimension is often overlooked in studies of economic growth, in addition, the effects of structural changes in neighboring regions can spread spatially and affect the growth of states. Taking that into account, this paper aims to make an analysis of the direct and indirect effects of structural change on the economic growth of the Brazilian states in the period from 1970 to 2010. Using a dynamic spatial panel model, this paper provides evidence that the structural change occurred in the country impacts the spatial economic growth of the Brazilian states. Our results confirm the importance of considering the spatial dependency in the model and show that there is a positive impact of structural change on Brazilian states’ GDP per capita. Also, we find evidence that there is a positive spatial spillover of structural change, human capital and urbanization on regional growth.